Regional variation in sentences for child sexual abuse: An empirical study with Finnish court data - Malin, Tiina (International journal of law, crime and justice, 2022)
While sentencing consistency is a major principle of most of the justice systems, some features of sentencing disparities remain understudied. The purpose of the current study is to examine regional variation in aggravation assessment of child sexual abuse (CSA). We use data of CSA convictions given in Finnish district courts (n = 909). Multilevel regression modeling is used as the analytic method to assess whether the variation persists even after controlling for the offense characteristics. The descriptive results show that there are remarkable differences between courts. The results from the multilevel regression analysis suggest that the between-court variation in convictions is not fully explained by the observed offense characteristics, as the variation persists even after controlling for these. While the current results are suggestive of between-court sentencing disparities, the source for this variation remains speculative. More research is needed on data allowing for both between- and within-court analyses.